Exploring perceptions of transformational leadership and group cohesion in the outdoor recreation curriculum at UiTM's Faculty of Sports Science and Recreation - Khairul Anuar, Siti Sarah (2025)
Outdoor recreation programs at the Faculty of Sports Science and Recreation (FSR), Universiti Teknologi MARA (UiTM), are integral to experiential learning, promoting leadership development, teamwork, and personal growth. Recognizing the importance of effective leadership and cohesive group dynamics in such settings, this study investigates students' perceptions of transformational leadership behaviours and their relationship with group cohesion in UiTM's outdoor recreation curriculum. Specifically, this research aims to: (i) identify students' perceptions of transformational leadership behaviours and group cohesion values within the curriculum, (ii) examine the relationship between the four dimensions of transformational leadership which are idealized influence, intellectual stimulation, inspirational motivation, and individual consideration, and elements of group cohesion, (iii) compare perceptions of transformational leadership behaviours between male and female students, and (iv) compare perceptions of group cohesion between male and female students. The study involved 230 UiTM students (120 male, 110 female) from various campuses and academie levels. Data were collected using the Multifactor Leadership Questionnaire (MLQ) 5x-short and the Group Environment Questionnaire (GEQ). Findings revealed a significant relationship between transformational leadership dimensions and two group cohesion factors: individual attraction to the group-task (ATG-T) and group integration-task (GI-T). however, no significant gender differences were found in students' perceptions of transformational leadership behaviours or group cohesion values. This research is important for FSR UiTM's curriculum development and instructional strategies. It highlights how transformational leadership can enhance group functioning, motivation, and collaborative learning in outdoor recreation contexts. By promoting such leadership traits, the faculty can cultivate more resilient, communicative, and adaptive student leaders capable of managing challenges in dynamic outdoor environments.